Historical Thinking Skills- The Forgotten Skills? - Rosy Talin (2015)
This article explains the discipline structure of History subject in Malaysia. The discipline consists of five concepts: Historical Inquiry, Historical Information Gathering, Historical Thinking Skills (HTS), Historical Explanation, Understanding History and Empathy. Among the five concepts, this article discusses HTS which has been specifically emphasizes in the curriculum. Inclusive in the discussion is the meaning of HTS and the skills it covers - Understanding Chronology, Discovering Historical Evidence, Interpretation, Imagination and Rationalize Facts; its present application in the teaching of history in the classroom, the possibility of its inculcation in the teaching, and the significance of HTS if taught to the younger generation. Keywords: Historical Thinking Skills, History Teaching, History Learning, Historical Inquiry